Palladium-catalyzed regiodivergent arylamination/aryloxygenation of allenamide. Issue 21 (26th September 2022) - Yang, Yi; Wang, Hui; Sun, Zehua; Li, Xinjin; Sun, Fenggang; Liu, Qing; Zhang, Lizhi; Xu, Liping; Liu, Hui
Abstract : In regiodivergent arylamination/aryloxygenation of allenamides, use of Cy2 NMe caused 2, 1-arylamination and the corresponding alkenes were formed with excellent Z configuration. Whereas, utilizing Ag2 CO3 caused 2, 3-aryloxygenation via an unexpected CO2 insertion from Ag2 CO3 . Abstract : A palladium-catalyzed multi-component regiodivergent arylamination/aryloxygenation of allenamide is reported. The bases are critical to the chemoselectivity and regioselectivity: (1) Cy2 NMe as a base could lead to distal addition that generated a 2, 1-arylamination product; (2) Ag2 CO3 as a base could result in proximal addition for a 2, 3-aryloxygenation product via a four-component transformation, including an unexpected CO2 insertion from Ag2 CO3 . Notably, the corresponding alkenes formed in 2, 3-arylamination could be presented with excellent Z configuration, which was modulated via the steric hindrance of a coordinated palladium intermediate. Two possible π-allyl-Pd complexes were proposed for the resulting regioselectivity: the neutral η 3 π-allyl-Pd complex favored the γ substitution where there was less steric hindrance; cationic η 1 π-allyl-Pd complex generated via the coordination of Ag favored the reductive elimination at the allylic position adjacent to nitrogen.